WOUND HEALING AND MANTLE REGENERATION IN Atrina vexillum (BIVALVIA : PINNIDAE) WITH ANESTHESIA 1-PHENOXY-2-PROPANOL - Polakitan, Chrisye L.; Mamangkey, N. Gustaf F.; Kaligis, Georis F. (JURNAL PESISIR DAN LAUT TROPIS, 2013)
In order to know the time of wound healing and regeneration on mantle ofÂ Atrina vexillum, 30 indivuals ofÂ Atrina vexillum were collected from the coast of Arakan village,Tatapaan Distric, Minahasa Selatan Regency. A distal portion (1x1 cm) on mantle fromthe left shell of each individual was cut off after the organisms were anasthetized using 1-Phenoxy-2-propanol. Two individuals were sampled every 1, 3, 6, 12 hours and 1, 3, 6,12 and 24 days and the ex-wounds were cut off for histological observation in laboratory.The result showed that the healing time of the wound started from three to twelve days ofthe observation and mantle regeneration was first detected from twelve to twenty fourdays of observation; then there was no mortality recorded during this study.